Preliminary incidence and trends of infections with pathogens transmitted commonly through food — Foodborne Diseases Active Surveillance Network, 10 U.S. sites, 2015–2018. Issue 6 (28th May 2019) - Tack, Danielle M.; Marder, Ellyn P.; Griffin, Patricia M.; Cieslak, Paul R.; Dunn, John; Hurd, Sharon; Scallan, Elaine; Lathrop, Sarah; Muse, Alison; Ryan, Patricia; Smith, Kirk; Tobin‐D'Angelo, Melissa; et al.
Abstract : Foodborne diseases present a major health problem in the United States in general, and transplant patients are at a higher risk from pathogens than the general population.